PERAN PEREMPUAN DALAM PENGELOLAAN SAMPAH DI KOTA SERANG - Fatmawati, Linda; Jaenul, Jaenul; Wulandari, Novi; Masripa, Masripa; Syarkawi, Syarkawi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Waste management has become a critical and pressing issue faced by many cities in Indonesia, including Serang City. Household waste continues to increase over time and remains inadequately processed. In this context, women as household managers hold a significant role that is often overlooked in policy formulation. This Community Service Program (PKM) was designed to expand the understanding, involvement, and capacity of women in community-based waste management. The methods used included socialization, participatory discussions, and gender-based education aimed at increasing awareness, capacity, and women’s engagement in sustainable waste practices. The results indicate that involving women can enhance collective awareness, reduce waste volume, and encourage sorting and reuse practices that support sustainable waste solutions.Keywords: Waste management; Women; Community participation.